Implementation of the item-based collaborative filtering method on a web-based culinary tourism recommendation system (case study: Magelang City) - Ahmad Husain Ardiansyah; Andi Widiyanto; Setiya Nugroho (Borobudur Informatics Review, 2022)
Culinary is a type of business that will always exist, this is because one of the factors of human needs is in the form of food. Therefore it is necessary to have a system that provides recommendations to provide input to consumers to minimize consumer confusion about the many culinary places. In this study, to obtain recommendations, the Item-based Collaborative Filtering method will be used to approach consumers with one another. Meanwhile, to get this approach, the approach that will be assessed is an approach to rating culinary places, to get a consumer rating it will give value to 4 aspects, namely: place value, service value, view value, and speed of service value. This study uses the consine similarity algorithm to get the value of the approach. The results obtained by this study using the Likert scale method got a value of 71.6656% "fulfilled". Meanwhile, in the black-box test, the score is 100% functioning, and in the test to determine the accuracy of manual calculations and the system, the value is 100% the same.